2002
DOI: 10.1002/jmv.10264
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin inhibits DNA, RNA, and protein synthesis in PHA‐stimulated human peripheral blood mononuclear cells: Possible explanation for therapeutic efficacy in patients with chronic HCV infection

Abstract: The treatment of choice for patients infected chronically with HCV is the combination of IFN-alpha and ribavirin. Monotherapy with ribavirin leads to a clinical and histological improvement, but its exact mechanism of action is unknown. Therefore, the effect of ribavirin on synthesis of inflammatory cytokines and on apoptosis in stimulated peripheral blood mononuclear cells (PBMCs) was investigated. PBMCs were isolated from the blood of HCV infected patients and from healthy volunteers. The effect of ribavirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…It is obvious that immune cells abnormalities were more frequent among HCV Egyptian patients receiving peg-IFNα-2a. Consistent with the current results, upon RBV administration, the rate of apoptotic CD14 + and CD45 + cells in PBMCs in vitro cultures were increased in a dose-dependent way (Meier et al, 2003). RBV administration induced STAT-1 DNA binding which may be rendered to the consequence of an enhanced STAT-1 tyrosine phosphorylation, enhanced STAT-1 synthetic rate, or an indirect effect caused by minimizing the expression of upstream STAT inhibitors (like STAT inhibitor II) (Zhang et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is obvious that immune cells abnormalities were more frequent among HCV Egyptian patients receiving peg-IFNα-2a. Consistent with the current results, upon RBV administration, the rate of apoptotic CD14 + and CD45 + cells in PBMCs in vitro cultures were increased in a dose-dependent way (Meier et al, 2003). RBV administration induced STAT-1 DNA binding which may be rendered to the consequence of an enhanced STAT-1 tyrosine phosphorylation, enhanced STAT-1 synthetic rate, or an indirect effect caused by minimizing the expression of upstream STAT inhibitors (like STAT inhibitor II) (Zhang et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies enumerated many adverse effects of peg-IFN α and/or RBV treatment on the immune status SOF chronically infected HCV patients (Arizcorreta et al, 2006;Kondo et al, 2013;Meier et al, 2003;Werner et al, 2014). DAAs were initially utilized in addition to peg-IFN α plus RBV, which amended SVR rates but at the expense of further restricting patient eligibility and incrementing the range of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-a is known to mediate anti-inflammatory effects [28] and inhibit leukocyte proliferation while modulating both T helper type 1 (Th1) and type 2 immune responses. RBV reduces liver inflammation and proliferation and to some extent the production of IFN-c by Th1 lymphocytes [29]. During previous studies by our group [30] and others [31], PegIFN-a/RBV were shown to exert a significant negative impact on HIV and/or CMV but not on HCV-specific Th1 immune responses.…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have reported that ribavirin has diverse effects on the cytokines produced by peripheral blood mononuclear cells stimulated with nonspecific mitogens (22,24,32,34). The results of these studies suggest that ribavirin enhances the production of some cytokines and inhibits the production of others.…”
Section: Discussionmentioning
confidence: 99%